2015
DOI: 10.1053/j.ajkd.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Urinary, Plasma, and Serum Biomarkers’ Utility for Predicting Acute Kidney Injury Associated With Cardiac Surgery in Adults: A Meta-analysis

Abstract: In adults, known urinary, plasma, and serum biomarkers of AKI possess modest discrimination at best when measured within 24 hours of cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
174
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(193 citation statements)
references
References 54 publications
4
174
1
8
Order By: Relevance
“…A recent meta-analysis by Ho et al including 16 studies with a total of 2906 patients investigated urine NGAL as a biomarker for the prediction of AKI after cardiac surgery in adult patients. The composite area under the receiver operating characteristic curve (AUC) of urine NGAL was 0.72 [23]. A recent study of patients with preeclampsia showed that measurement of NGAL was not a suitable diagnostic test for AKI [25].…”
Section: Biomarkers Of Akimentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis by Ho et al including 16 studies with a total of 2906 patients investigated urine NGAL as a biomarker for the prediction of AKI after cardiac surgery in adult patients. The composite area under the receiver operating characteristic curve (AUC) of urine NGAL was 0.72 [23]. A recent study of patients with preeclampsia showed that measurement of NGAL was not a suitable diagnostic test for AKI [25].…”
Section: Biomarkers Of Akimentioning
confidence: 99%
“…Furthermore, biomarkers 0. 72 Cardiac surgery in adults [23] 0.75 ICU [30] IL-18 A 24-kDa cytokine from the IL-1 family of cytokines (regulates innate and adaptive immunity) 0.64 Emergency department [20] No certain prediction of AKI in adults [10] 0.82 Pediatric cardiac surgery [31] 0.59…”
Section: Introductionmentioning
confidence: 99%
“…Urinary L-FABP can predict the onset of AKI after cardiac surgery [13,49,50], pediatric cardiopulmonary bypass [17], stem cell transplantation [12], and endovascular and open-abdominal aortic aneurysm repair [16] as well as in intensive care unit populations [15]. Additionally, L-FABP can also predict the progression to end-stage renal disease (ESRD), the onset of cardiovascular disease (CVD), or death for patients with AKI [14,51], type 2 diabetes [8,52], or chronic kidney a b Fig.…”
Section: Predicting Poor Outcomesmentioning
confidence: 99%
“…Both functional biomarkers and markers of injury have been identified which detect subclinical insult or facilitate the diagnosis of AKI early [6]. Unfortunately, following initial enthusiasm, it has become clear that most biomarkers have important shortcomings and limited utility at the bedside [7,8]. There are several potential explanations for their disappointing performance in clinical studies, including lack of a gold standard to define AKI, inclusion of patients with already overt AKI and absence of relevant patient outcomes.…”
Section: Predicting Akimentioning
confidence: 99%